Arsenic toxicity in Antarctic krill oil and its impact on human intestinal cells - Haiyan Zhang; Yunyun Ji; Zhongquan Jiang; Guangxin Yang; Cong Kong; Zhemin Shen; Tao Yuan; Xiaosheng Shen (Ecotoxicology and Environmental Safety)
Arsenic is a pervasive environmental pollutant that can bioaccumulate in Antarctic krill through the food chain, posing potential risks to human health. This study investigates the toxic effects of arsenic in Antarctic krill oil (AKO) on Caco-2 cells, focusing on oxidative stress and apoptosis induction. AKO is nutrient-rich and contains various arsenic species, including arsenite (As³⁺), arsenate (As⁵⁺), dimethyl arsinic acid (DMA), and arsenobetaine (AsB), each exhibiting different toxic potencies. Caco-2 cells were treated with arsenic standards and AKO to assess cell viability, lactate dehydrogenase (LDH) release, oxidative stress markers (superoxide dismutase [SOD], catalase [CAT], malondialdehyde [MDA], and glutathione peroxidase [GSH-Px]), reactive oxygen species (ROS) production, and apoptosis. Results demonstrated dose-dependent cytotoxicity, with As³ ⁺ being the most toxic, followed by As⁵⁺, DMA, and AsB. After 24 hours of exposure, cell viability in the high-concentration AKO group decreased to 63.95 %. Arsenic exposure elevated ROS levels, disrupted mitochondrial membrane potential, upregulated apoptosis-related genes such as Caspase-3, Caspase-9, and Bax, and downregulated the PI3K/AKT/mTOR signaling pathway. This study elucidates the mechanisms underlying arsenic toxicity in AKO and underscores its implications for food safety assessments.